Estudo da adição de diferentes prebióticos em micropartículas simbióticas contendo Lactobacillus acidophilus LA-5 obtidas por gelificação iônica interna - Raddatz, Greice Carine (2018)
Probiotics have been given increasing focus in the area of foods, since they can beneficially affect one or more target functions in the body when administered in adequate amounts. However, the viability of these cultures may be impaired when exposed to adverse conditions such as storage at different temperatures and passage through the human gastrointestinal tract. As a result, it is necessary to study and implement new techniques that guarantee the production of these in a large scale and with proven beneficial effects, making it possible to meet consumer needs. In order for the product to guarantee the desired beneficial effect, the microencapsulation technique is commonly used. Among the various techniques of microencapsulation is the internal ionic gelation. Also for probiotic viability to be longer, the effect of prebiotics on microencapsulation has been studied. Thus, the objective of this study was to develop pectin microparticles (1%) and to compare them with pectin microparticles added from different prebiotic sources at 10%, being hi-maize, inulin and rice bran, both containing Lactobacillus acidophilus LA -5 using the internal ionic gelation technique. The microparticles were produced in wet and freeze-dried form. The survival of probiotics under simulated gastrointestinal conditions, their viability in storage under different temperatures (-18, 7 and 25 ° C) for 120 days, in addition to their physico-chemical characterization, morphology and size distribution were analyzed. For the moist microparticles, there was a size variation of 24.4-462 μm, meanwhile, the size of the lyophilized microparticles ranged from 166 μm to 345 μm. The encapsulation matrices of rice bran and inulin had the highest encapsulation efficiency for the moist microparticles of 91.24% and 90.59%, respectively. For the lyophilized microparticles, the highest encapsulation efficiency was due to the pectin + inulin encapsulation matrix, of 68.11%. Both the moist and lyophilized microparticles of all treatments protected the microorganisms against the simulated gastrointestinal tests. In relation to storage at different temperature conditions, for moist microparticles at 25 ° C, probiotics remained viable in all treatments over the course of 120 days. At the temperature of -18 ° C, the PHM and PRB treatments were able to keep the microorganism viable for a longer time period, of 90 days. At 7 ºC the PRB treatment stood out, remaining viable at the end of the 120 days. For lyophilized particles, at temperatures of 25 ° C and -18 ° C, treatments containing prebiotics maintained viable probiotic microorganisms for a longer period of time. At 7 ° C, PRBL treatment was able to maintain L. acidophilus viable for 120 days. Thus, the microparticles developed in this study, besides allowing an extended viability of the probiotic L. acidophilus, represent a viable alternative for the incorporation of symbiotics in food matrices.